TECHNOLOGICAL FLOW IN ULTRASONIC WELDING OF COPPER CONDUCTORS USED IN THE AUTOMOTIVE FIELD (Nonconventional Technologies Review, 2025)
Ultrasonic welding is the new method used in industry for a wide range of operations: assembly of wire harnesses and heavy cables for cars, trucks and industrial machines, assembly of solar cells that constitute solar panels, welding of larger metal parts, spot welding - including wire-to-terminal welding - in a single impulse, fast and clean joining of thin aluminium and copper foils and last but not least the precise crimping and sealing of copper and aluminium tubes. The current work wants to present this system by presenting a case study. Compared to crimping or pressure welding, this process offers numerous advantages. In addition to the excellent electrical properties of the joint and extremely low energy consumption, this method is particularly characterized by complete process control and process data management.
Keywords: welding; ultrasound; copper; flow